Brain tissue oxygen guided treatment supplementing ICP/CPP therapy after traumatic brain injury. Issue 6 (1st June 2003) - Meixensberger, J; Jaeger, M; Väth, A; Dings, J; Kunze, E; Roosen, K
Abstract : Objective: To evaluate the effects of a brain tissue oxygen (Pti o 2 ) guided treatment in patients with traumatic brain injury. Methods: Pti o 2 was monitored in 93 patients with severe traumatic brain injury. Forty patients admitted from 1993 to 1996 were treated with intracranial pressure/cerebral perfusion pressure (ICP/CPP) management alone (ICP < 20 mm Hg, CPP > 70 mm Hg). Fifty three patients admitted from 1997 to 2000 were treated using ICP/CPP management, but in this second group CPP was also increased as individually required to raise the Pti o 2 above 1.33 kPa (10 mm Hg) (Pti o 2 guided group). Results: Cerebral hypoxic phases with Pti o 2 values below 1.33 kPa occurred significantly less often in the Pti o 2 guided group. Pti o 2 values were higher over the whole monitoring period. No statistical differences could be observed in outcome at six months, despite a positive trend in the Pti o 2 guided group. Conclusions: Cerebral hypoxic events can be reduced significantly by increasing cerebral perfusion pressure as required. To show a clear beneficial effect of Pti o 2 guided cerebral perfusion pressure management on outcome, a multicentre randomised trial needs to be undertaken.